Expressions of domestic violence against adolescents: Educators' speeches - Kátia Cordélia Cunha Cordeiro; Nadirlene Pereira Gomes; Luana Moura Campos; Jéssica Damasceno de Santana; Rosana Santos Mota; Climene Laura de Camargo
ABSTRACT Objectives: to describe the expressions recognized by domestic violence educators experienced by school adolescents. Methods: it is a qualitative study based on Paulo Freire's liberating pedagogy. Semi-structured interviews were conducted with 20 teachers from a public elementary school in the city of Salvador, state of Bahia, Brazil. The data were systematized through the Discourse of the Collective Subject. Results: collective discourse reveals that educators identify schoolchildren who experience physical, psychological and negligent abuse, being denied even love and affection. Conclusions: although not alluding to sexual abuse, educators recognize that students are inserted in the context of domestic violence, knowledge necessary for the development of actions that enable the exit of the student from the oppressed and overcoming the lived experience.